2014
DOI: 10.3171/2014.6.jns132285
|View full text |Cite
|
Sign up to set email alerts
|

Awake craniotomy for gliomas in a high-field intraoperative magnetic resonance imaging suite: analysis of 42 cases

Abstract: Object. The object of this study was to describe the experience of combining awake craniotomy techniques with high-field (1.5 T) intraoperative MRI (iMRI) for tumors adjacent to eloquent cortex.Methods. From a prospective database the authors obtained and evaluated the records of all patients who had undergone awake craniotomy procedures with cortical and subcortical mapping in the iMRI suite. The integration of these two modalities was assessed with respect to safety, operative times, workflow, extent of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 24 publications
1
39
2
2
Order By: Relevance
“…The rate of GTR achieved in our study is similar to the rates reported previously. 16,19,21,33,35 Although OS and PFS were different between the LGG and HGG groups, the relatively short observational period (a mean of 24.8 months) prevents us from making any definitive conclusion for the LGG group based on these results. Nonetheless, to our knowledge this is the first study to analyze the clinical outcomes, and the follow-up period is considerably longer than in the previous reports.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The rate of GTR achieved in our study is similar to the rates reported previously. 16,19,21,33,35 Although OS and PFS were different between the LGG and HGG groups, the relatively short observational period (a mean of 24.8 months) prevents us from making any definitive conclusion for the LGG group based on these results. Nonetheless, to our knowledge this is the first study to analyze the clinical outcomes, and the follow-up period is considerably longer than in the previous reports.…”
Section: Discussionmentioning
confidence: 78%
“…They also enhance the rate of complete tumor resection by providing surgeons with updated information, allowing them to precisely localize tumor remnants intraoperatively and guide their resection accordingly. 10,17,21,25,31,36 Specifically, the application of iMRI for patients with glioma continues to expand because it can enable maximal resection while maintaining the integrity of uninvolved brain tissue. 12,17,36 Nonetheless, as depicted in a recent Cochrane Review, first-level evidence for the clinical applications of such expensive technologies is still lacking and there is no clear answer with regard to the overall benefit in terms of survival and quality of life (QOL).…”
mentioning
confidence: 99%
“…The AC procedure was developed to allow greater resection with less risk of damaging eloquent cognitive brain functions [1,[13][14][15]. There is limited evidence regarding the best anesthesia technique for resecting these insular tumors, and the number of patients in published articles is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de equipamento intraoperatório presente apenas em centros de referência e com altos custos de realização. Ademais, há claras limitações técnicas como longo tempo necessário para aquisição de imagens, necessidade de técnicas anestésicas especiais, interferências instrumentais (Maldaun et al 2014).…”
Section: Resultsunclassified